Risk of out-of-hospital cardiac arrest in patients with bipolar disorder or schizophrenia. Issue 19 (15th January 2021) - Barcella, Carlo Alberto; Mohr, Grimur; Kragholm, Kristian; Christensen, Daniel; Gerds, Thomas A; Polcwiartek, Christoffer; Wissenberg, Mads; Bang, Casper; Folke, Fredrik; Torp-Pedersen, Christian; Kessing, Lars Vedel; Gislason, Gunnar Hilmar; et al.
Abstract : Objective: Patients with bipolar disorder and schizophrenia are at high cardiovascular risk; yet, the risk of out-of-hospital cardiac arrest (OHCA) compared with the general population remains scarcely investigated. Methods: We conducted a nested case-control study using Cox regression to assess the association of bipolar disorder and schizophrenia with the HRs of OHCA of presumed cardiac cause (2001–2015). Reported are the HRs with 95% CIs overall and in subgroups defined by established cardiac disease, cardiovascular risk factors and psychotropic drugs. Results: We included 35 017 OHCA cases and 175 085 age-matched and sex-matched controls (median age 72 years and 66.9% male). Patients with bipolar disorder or schizophrenia had overall higher rates of OHCA compared with the general population: HR 2.74 (95% CI 2.41 to 3.13) and 4.49 (95% CI 4.00 to 5.10), respectively. The association persisted in patients with both cardiac disease and cardiovascular risk factors at baseline (bipolar disorder HR 2.14 (95% CI 1.72 to 2.66), schizophrenia 2.84 (95% CI 2.20 to 3.67)) and among patients without known risk factors (bipolar disorder HR 2.14 (95% CI 1.09 to 4.21), schizophrenia HR 5.16 (95% CI 3.17 to 8.39)). The results were confirmed in subanalyses only including OHCAs presenting with shockable rhythm or receiving an autopsy. Antipsychotics—but not antidepressants, lithium or antiepileptics (the last two only tested in bipolar disorder)—increased OHCA hazard compared with no use in both disorders. Conclusions: Patients with bipolar disorder or schizophrenia have a higher rate of OHCA compared with the general population. Cardiac disease, cardiovascular risk factors and antipsychotics represent important underlying mechanisms.